2013
DOI: 10.1038/mp.2013.30
|View full text |Cite
|
Sign up to set email alerts
|

Altered gene expression in the dorsolateral prefrontal cortex of individuals with schizophrenia

Abstract: The underlying pathology of schizophrenia (SZ) is likely as heterogeneous as its symptomatology. A variety of cortical and subcortical regions, including the prefrontal cortex, have been implicated in its pathology, and a number of genes have been identified as risk factors for disease development. We used in situ hybridization (ISH) to examine the expression of 58 genes in the dorsolateral prefrontal cortex (DLPFC, comprised of Brodmann areas 9 and 46) from 19 individuals with a premorbid diagnosis of SZ and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
82
5

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(88 citation statements)
references
References 80 publications
1
82
5
Order By: Relevance
“…By contrast, PV transcript levels are normal in patients with MDD (Guilloux et al, 2012; Rajkowska et al, 2007; Sibille et al, 2011). However, reduced expression of SST is not exclusively found in MDD but has also been reported for schizophrenia (Guillozet-Bongaarts et al, 2014; Morris, Hashimoto, & Lewis, 2008). Collectively the data suggest that at the cellular and molecular level GABAergic deficits associated with schizophrenia and MDD include both disease-specific and common characteristics.…”
Section: The Gabaergic Deficit Hypothesis Of Mddmentioning
confidence: 83%
“…By contrast, PV transcript levels are normal in patients with MDD (Guilloux et al, 2012; Rajkowska et al, 2007; Sibille et al, 2011). However, reduced expression of SST is not exclusively found in MDD but has also been reported for schizophrenia (Guillozet-Bongaarts et al, 2014; Morris, Hashimoto, & Lewis, 2008). Collectively the data suggest that at the cellular and molecular level GABAergic deficits associated with schizophrenia and MDD include both disease-specific and common characteristics.…”
Section: The Gabaergic Deficit Hypothesis Of Mddmentioning
confidence: 83%
“…Chromosomal copy number variants in the CHRNA7 region, some isolating the gene itself, have been found in all three illnesses, along with positive association studies and genetic linkage (6–8). CHRNA7 is the most significantly decreased neocortical mRNA in schizophrenia, and it is decreased in ASD as well (9, 10). The aim of this study was to assess whether this genetic diathesis can be mitigated by an intervention during perinatal brain development.…”
mentioning
confidence: 99%
“…26 The peptide was also increased following chronic stress 28 or amphetamine administration 29 in rodents, whereas clinical gene expression studies found it to be increased in one study of patients with mental illness 30 but reduced in another. 31 Peaks that were similarly upregulated in the hippocampus and cortex (m/z 1201.9, 1450.2, 1583.1 and 1907.3) were putatively identified as a phosphosphingolipid, a glycerophosphoglycerophosphoglycerol, an acidic glycosphingolipid and a neutral glycosphingolipid, respectively, using the Nature Lipidomics Gateway informatics platform (see Supplementary Methods for details). Further studies are needed to fully identify and evaluate these and other results in the data set.…”
Section: Resultsmentioning
confidence: 99%